2010
DOI: 10.1097/hjh.0b013e328335c34f
|View full text |Cite
|
Sign up to set email alerts
|

Reduced cerebral blood flow in older men with higher levels of blood pressure

Abstract: Objective-Examine relations of blood pressure (BP) to single photon emission computed tomography (SPECT)-derived estimates of cerebral blood flow in older men and women.Methods-Seventy-four stroke and dementia-free, community-dwelling older adults (ages 54-83; 68% men; 91% White) free of major medical, neurological, or psychiatric disease, engaged in a) clinical assessment of resting systolic and diastolic BP; b) magnetic resonance imaging (MRI) rated for brain atrophy; and c) brain SPECT studies with computer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
31
2
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 26 publications
4
31
2
2
Order By: Relevance
“…These may be later manifestations of progression toward hypertension given the age of our participants and the two-year follow-up. While we only observed trends, others have found progression of BP over ten years of follow-up to relate to enlarged ventricles 35 and declines in overall CBF 36 37. .…”
Section: Discussioncontrasting
confidence: 67%
“…These may be later manifestations of progression toward hypertension given the age of our participants and the two-year follow-up. While we only observed trends, others have found progression of BP over ten years of follow-up to relate to enlarged ventricles 35 and declines in overall CBF 36 37. .…”
Section: Discussioncontrasting
confidence: 67%
“…29 Another study, not only in a healthy but also younger population (mean age, 67 years), showed that only in men higher BP was associated with lower CBF. 30 However, no association between low BP and reduced CBF was found in any of these studies. Furthermore, higher BP among persons with atherosclerosis was associated with a decline in CBF during 5-year follow-up, 31 and previous findings in hypertensive older persons aged ≥70 years showed that CBF increased in persons who were more intensively treated for hypertension.…”
Section: Discussionmentioning
confidence: 70%
“…27 Narrowing of the vessel lumen and an increased wall/lumen ratio are typically demonstrated in animal models 8,28,29 and humans with hypertension. 9,30 Furthermore, cerebral blood flow is attenuated in elderly patients with hypertension 31,32 and is related to white matter lesions 33 and small vessel disease, 34 a finding which is contradictory to studies indicating that cerebral autoregulation is intact in hypertensive patients. 35 Our data are the first to show that in middle-aged hypertensive humans without cerebral stenotic disease, total arterial cerebral blood flow (Table 1) and cerebral perfusion in all brain regions measured (Table 3) are lower compared with age-matched normotensive participants.…”
Section: Discussionmentioning
confidence: 93%